1996
DOI: 10.2169/internalmedicine.35.941
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cisapride on the Pharmacokinetics and Antihypertensive Effect of Sustained-Release Nifedipine.

Abstract: To investigate the clinical significance of interactions between cisapride and sustained-release nifedipine, we comparedthe plasma nifedipine concentration and blood pressure after administration of nifedipine alone (20 mg) with those obtained after administration of nifedipine with cisapride (2.5 mg) in 20 patients with hypertension. The plasma nifedipine level was not altered by cisapride at one hour after administration, but was significantly increased at two (p<0.01), three (p<0.01), and four (p<0.05) hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 22 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…It is frequently given in combination with other drugs. Satoh et al (1996) reported that there are significant pharmacokinetic interactions between cisapride and some other drugs.…”
Section: Introductionmentioning
confidence: 99%
“…It is frequently given in combination with other drugs. Satoh et al (1996) reported that there are significant pharmacokinetic interactions between cisapride and some other drugs.…”
Section: Introductionmentioning
confidence: 99%